2017
DOI: 10.1111/jors.12335
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration economies and the location of foreign direct investment: A meta‐analysis

Abstract: This paper undertakes a meta-analysis of the effect of agglomeration economies on foreign direct investment (FDI) location. It finds strong differences in these economies arising from both measurement and study-specific characteristics. Economies generated from domestic rather than foreign activity have the strongest effects on FDI, with the latter only significant if related to the home country of the investor. Support is also found for studies that identify different sources of agglomeration economies, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 143 publications
(112 reference statements)
1
13
0
3
Order By: Relevance
“…One of the phenomena that has been most researched in the current literature on location choice is FDI agglomerations. Jones (2017), found that the majority of the studies focus on analysing the effect and externalities of agglomeration economies on FDI and/or the reasons why the firms decide to co-locate with other firms, especially with those with the same activity (industrial clusters). Wu et al (2017) have examined how host country institutional factors influence agglomeration and they found that foreign firms respond to institutional pressures by agglomerating in countries characterized by collectivism and economic and political uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…One of the phenomena that has been most researched in the current literature on location choice is FDI agglomerations. Jones (2017), found that the majority of the studies focus on analysing the effect and externalities of agglomeration economies on FDI and/or the reasons why the firms decide to co-locate with other firms, especially with those with the same activity (industrial clusters). Wu et al (2017) have examined how host country institutional factors influence agglomeration and they found that foreign firms respond to institutional pressures by agglomerating in countries characterized by collectivism and economic and political uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, provided that the prevailing FDI strategy is the same as in our case‐study and therefore there exists complementary of FDI, the recommendation of designing joint strategies at regional level could also be accepted for other countries. In addition, as the presence of agglomeration is a feature of FDI not only in Spain but also in most countries (Jones ), it is obvious that the attractiveness degree of regions depends on their geographical location and that our conclusion stating that some regions should strive more than others to entice FDI holds. The type of effort described here is not, however, applicable to every country; it should be qualified depending on the FDI strategy that predominates.…”
Section: Discussionmentioning
confidence: 72%
“…As controls, agglomeration terms from industrial linkages are included for each of the foreign and domestic sectors, where the former is based on the number of FDI projects in the previous period and the latter on employment data (see Appendix Table A). A Jacobs term is added for industrial diversity for the linkages that go across industries (Jones, 2017), as well as a market structure term for the ease of entry into an industry. EU Structural Funds might attract FDI (Basile et al., 2008), but these could just signal that a country is underdeveloped.…”
Section: Data and Variablesmentioning
confidence: 99%